2019
DOI: 10.1360/ssc-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of bio-based polymer flame retardant coating

Abstract: Hierarchically spacing DNA probes on bio-based nanocrystal for spatial detection requirements Science Bulletin 64, 934 (2019); Design and synthesis by redox polymerization of a bio-based carboxylic elastomer for green tire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…After phosphorylation and self-assembly treatment, the introduction of the phosphate group leads to lower T onset and higher char residues of P-MCC, P-MCC@CS, and P-MCC@CS@PA-Na due to the catalytic dehydration and carbonization of MCC. 47 In addition to a high char residue of 35.5 wt % at 800 °C, P-MCC@CS@PA-Na shows higher T onset and T max than P-MCC and P-MCC@CS because of the contribution of phytate (PA) to thermal stability, 48 indicating satisfactory thermal stability. Therefore, the excellent charring ability and a high P content enable P-MCC@CS@PA-Na to improve the thermal stability and flame retardancy of EP by playing a role in both the gas and condensed phases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After phosphorylation and self-assembly treatment, the introduction of the phosphate group leads to lower T onset and higher char residues of P-MCC, P-MCC@CS, and P-MCC@CS@PA-Na due to the catalytic dehydration and carbonization of MCC. 47 In addition to a high char residue of 35.5 wt % at 800 °C, P-MCC@CS@PA-Na shows higher T onset and T max than P-MCC and P-MCC@CS because of the contribution of phytate (PA) to thermal stability, 48 indicating satisfactory thermal stability. Therefore, the excellent charring ability and a high P content enable P-MCC@CS@PA-Na to improve the thermal stability and flame retardancy of EP by playing a role in both the gas and condensed phases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…MCC owns a high initial thermal temperature ( T onset , 308.6 °C) and a low char residue at 800 °C (5.0 wt %). After phosphorylation and self-assembly treatment, the introduction of the phosphate group leads to lower T onset and higher char residues of P-MCC, P-MCC@CS, and P-MCC@CS@PA-Na due to the catalytic dehydration and carbonization of MCC . In addition to a high char residue of 35.5 wt % at 800 °C, P-MCC@CS@PA-Na shows higher T onset and T max than P-MCC and P-MCC@CS because of the contribution of phytate (PA) to thermal stability, indicating satisfactory thermal stability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zhaoqing Lu, Wenjing Hu et al ( Wu and Ma, 2021 ) used the sol-gel method to prepare the surface modification method of nano-SiO2 coated aramid fiber. The study found that a dense nano-SiO2 coating layer is formed on the surface of the modified aramid staple fiber, the friction and wear resistance of the fiber material are effectively improved.…”
Section: The Development Of Cut-resistant Textile Materialsmentioning
confidence: 99%